ChemInform Abstract: Highly Efficient and Stable Cadmium Chalcogenide Quantum Dot/ZnO Nanowires for Photoelectrochemical Hydrogen Generation. Issue 19 (18th April 2013) - Seol, Minsu; Jang, Ji‐Wook; Cho, Seungho; Lee, Jae Sung; Yong, Kijung
Abstract The oxygen‐evolution catalyst IrOx·nH2O is used to modify a CdSe/CdS quantum dot cosensitized ZnO nanowire photoanode in a photoelectrochemical hydrogen generation system.